27th AIAA Applied Aerodynamics Conference 2009
DOI: 10.2514/6.2009-4105
|View full text |Cite
|
Sign up to set email alerts
|

Roughness Based Crossflow Transition Control: A Computational Assessment

Abstract: A combination of parabolized stability equations and secondary instability theory has been applied to a low-speed swept airfoil model with a chord Reynolds number of 7.15 million, with the goals of (i) evaluating this methodology in the context of transition prediction for a known configuration for which roughness based crossflow transition control has been demonstrated under flight conditions and (ii) of analyzing the mechanism of transition delay via the introduction of discrete roughness elements (DRE). Rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Also, for this configuration, NPSE solutions confirmed the experimental observations (cf. Li et al 2009). …”
Section: Introductionmentioning
confidence: 93%
“…Also, for this configuration, NPSE solutions confirmed the experimental observations (cf. Li et al 2009). …”
Section: Introductionmentioning
confidence: 93%
“…In addition, for monitoring the development of secondary instability using NPSE, 5 Fourier modes are used to resolve the time evolution, i.e., m ranges from −5 to 5. Previous experiences with and tests on similar problems 18,19,31,32 show that the grid resolutions described above are sufficient to resolve all relevant scales up to the transition location for the problems at hand.…”
Section: Flow Configuration and Analysis Codesmentioning
confidence: 95%
“…Figure 3(a) shows comparisons of the nonlinear development of stationary and traveling crossflow vortices of the same spanwise wavelength (λ z = 8 mm) and the same initial amplitude (A init = 1 × 10 −5 ). This particular spanwise wave length was chosen because the linear and nonlinear PSE computations by Li et al 31,32 had indicated the crossflow vortex with λ z = 8 mm to be one of the most likely stationary modes to cause transition. The essential results of Ref.…”
Section: A Nonlinear Evolution Of a Traveling Crossflow Modementioning
confidence: 99%
See 1 more Smart Citation
“…24 in the context of modeling transition delay via discrete roughness elements (DREs). By applying the same methodology in the absence of any DREs, transition onset location was predicted to shift downstream by approximately 15 percent of the chord length for each orderof-magnitude reduction in the initial amplitude of the dominant 4.5mm stationary crossflow mode.…”
Section: Vb4 Random Surface Roughness: Disturbance Growthmentioning
confidence: 99%